Check the attached file for the solution.

**Answer:**

75

**Step-by-step explanation:**

f(1) = 7

f(n) = 3f(n-1) + 3

So what you are trying to do here is find the recursive value (that's what it is called) for f(n). Computers love this sort of thing, but we humans have to do it slowly and carefully.

So let's try f(2)

That means that f(2) = 3*f(n-1) + 3

but if f(2) is used it means that you have to know f(2-1) which is just f(1) and we know that.

so f(2) = 3*f(1)+3

f(2) = 3*7 + 3

f(2) = 21 + 3

f(2) = 24

Now do it again. We now know F(2), so we should be able to find f(3)

f(3) = 3*f(3 - 1) + 3

f(3) = 3*f(2) + 3 We know that f(2) = 24

f(3) = 3* 24 + 3

f(3) = 72 + 3

f(3) = 75

**Answer:**

5 and 50

**Step-by-step explanation:**

Constant of proportionality=(10-5)/(2-1)=5

Distance is 5*10=50